Efecto residual de los distintos niveles de (Trichanthera gigantea) sobre la funcionalidad espermática en verracos mestizos - Mejía Pinargote, Gema Milena (2024)
Seminal quality is crucial in artificial insemination programs for high genetic value swine. Therefore, this study focused on evaluating the residual effect of Trichanthera gigantea when added to the diet to analyze changes in the sperm quality parameters of crossbred boars, using three treatments: one control (0%), treatment 2 (10%), and treatment 3 (15%). The research was conducted at the teaching, research, and outreach unit “Hato Porcino” at ESPAM MFL, where three crossbred boars were evaluated under standardized feeding and management conditions. Various seminal quality parameters were analyzed, including motility, concentration, pH, and sperm morphology, using a completely randomized experimental design with an alpha value of 0.05, three treatments, and four replications. The results obtained for sperm motility variables throughout the study showed (P value <0.889), while concentration presented (P value <0.746). The pH demonstrated (P value <0.329). Regarding the variables of cellular malformations, the following values were found: head (P value <0.358), tail (P value <0.333), GCP (P value <0.985), GCM (P value <0.798), and GCD (P value <0.798). These results indicate that there are no significant differences in the seminal quality of the boars (p > 0.05). This suggests that the inclusion of Trichanthera gigantea in the diet did not have a notable residual effect on seminal quality.